FIRST REPORT OF SITTING ANOMOEPUS TRACKS IN EUROPEAN LOWER JURASSIC (LAVINI DI MARCO SITE - NORTHERN ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2001)
The palaeontologic site at Lavini di Marco, near to Rovereto (Trento), reveals a wide fossil tidal flat of Early Jurassic age (Calcari Grigi Formations – lower Member; Hettangian to lower Sinemurian ). An extensive set of dinosaur prints were discovered a few years ago and are now the subject of ichnological and paleobiological studies. The prints which are described in present short note are believed to represent the right and left foot of the same individual, set in a side-by-side, sub-parallel, sitting posture. The prints can be classified as Anomoepus Hitchcock 1848. Amongst recognised ichnospecies, most of the charachteristics of the prints here described point to Moyenisauropus dodai Ellenberger 1974 (recte Anomoepus dodai Olsen & Galton 1984) of Lesotho. By contrast, the prints found at Lavini di Marco differ from the Anomoepus found in central-east Europe. These characters would seem to confirm the Gondwanic origins of the Rovereto ichnofauna as previously supposed from the study of other taxa.